2003
DOI: 10.1007/s00381-003-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Split cord malformation and situs inversus totalis: case report and review of the literature

Abstract: Recent compelling evidence from animal models and human case reports has led to hypotheses that defects of the midline and laterality defects (e.g., situs inversus) are etiologically related. Confirmation from additional case reports of situs inversus and split cord malformation could prove useful in determining a genetic locus for split cord malformations or implicating various chemical agents that are known to produce situs inversus as potential causative factors in the production of split cord malformations. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Disturbances of normal asymmetric placement of organs, such as situs inversus or polysplenia, have been defined traditionally as laterality defects. However, recent evidence from vertebrate models and few cases of human birth defects [6][7][8] demonstrates that defects of laterality frequently are associated and etiologically related to other complex midline anomalies, both of which result from a disturbance of pattern formation during blastogenesis. This explains the association of TCD, occipital encephalocele and situs inversus in the present case.…”
Section: Discussionmentioning
confidence: 97%
“…Disturbances of normal asymmetric placement of organs, such as situs inversus or polysplenia, have been defined traditionally as laterality defects. However, recent evidence from vertebrate models and few cases of human birth defects [6][7][8] demonstrates that defects of laterality frequently are associated and etiologically related to other complex midline anomalies, both of which result from a disturbance of pattern formation during blastogenesis. This explains the association of TCD, occipital encephalocele and situs inversus in the present case.…”
Section: Discussionmentioning
confidence: 97%
“…This theory is supported by these authors, in which both types of SCMs (i.e., Types I and II) were identified in one of their patients. There may be a remote association between SCMs and situs inversus totalis (Tubbs et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Schlösser et al [ 13 ] reported the prevalence of scoliosis in patients with situs inversus totalis reached 8%, which is significantly higher than the normal population (1.5–3%), indicating that the 2 diseases may share a common physicochemical or molecular biological basis. Tubbs et al [ 14 ] presented a case of split cord malformation combined with situs inversus totalis and reviewed the relevant literature and found that multiple deformities were usually observed in this group of patients. Therefore, they made a hypothesis that multiple abnormalities may share a common initial factor.…”
Section: Discussionmentioning
confidence: 99%